2016
DOI: 10.1007/s10961-016-9469-4
|View full text |Cite
|
Sign up to set email alerts
|

When should a firm collaborate with research organizations for innovation performance? The moderating role of innovation orientation, size, and age

Abstract: Little is known about the conditions strengthening or weakening the impact of a firm's collaboration with research organizations on innovation performance. Thus, this study uses a sample of 542 manufacturing firms in Korea to examine how innovation orientation and firm size and age as internal characteristics influence the relationship between collaboration with research organizations and innovation performance. The results show that collaboration with research organizations has a positive impact on innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 74 publications
1
29
1
Order By: Relevance
“…The results also indicate that firm size (based on investment) does not moderate the relationship between INO and business performance. The findings are consistent with Yu and Lee (2017). The INO scale was developed and validated using the scale development procedure suggested by Churchill (1979).…”
Section: Discussionsupporting
confidence: 67%
“…The results also indicate that firm size (based on investment) does not moderate the relationship between INO and business performance. The findings are consistent with Yu and Lee (2017). The INO scale was developed and validated using the scale development procedure suggested by Churchill (1979).…”
Section: Discussionsupporting
confidence: 67%
“…Seo et al found that the partnerships of R&D can influence innovation performance, and this relationship is different among companies with different technical levels [23]. Yu and Lee found that research organizations can bring more motivations to the innovation performance of partner enterprises [24]. Najafi-Tavani et al analyzed the impact of collaborative innovation networks on innovation performance, proposing that partnerships between firms and research organizations can promote innovation performance under competitive environment [25].…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Prasad and Junni (2017) explored that organizational size moderated the effect of CEO psychological characteristics on firm innovativeness. Yu and Lee (2017) revealed that firm size was a moderator in the relationship between collaboration with research organizations and innovation performance in manufacturing firms. Petruzzelli et al's (2018) study in biotechnology firms showed that there was a moderating effect of firm size on the relationship between knowledge maturity and innovation value.…”
Section: Potential Moderating Role Of Firm Sizementioning
confidence: 99%